Food Systems Dashboard: How it will work - Fanzo, Jessica; Haddad, Lawrence (2020)
Jessica Fanzo and Lawrence Haddad POLICY SEMINAR Food Systems Dashboard: How it will work Co-Organized by IFPRI, CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), Global Alliance for Improved Nutrition (GAIN), and Johns Hopkins University (JHU) JAN 27, 2020 - 12:15 PM TO 01:45 PM EST